2013
DOI: 10.1186/1476-511x-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dietary omega-3/omega-6 fatty acid ratios on reproduction in male rats

Abstract: BackgroundBeneficial effects of omega-3 polyunsaturated fatty acids (n-3 PUFAs) on the reproduction of male animals are widely described in the literature. However, there is little information about the effect of n-3/n-6 PUFA ratios on male health and reproduction. The aim of this study was to investigate the effects of diets with different n-3/n-6 PUFA ratios on the reproductive performance of male rats.MethodsEighty male Sprague Dawley (SD) rats were supplemented with diets containing different n-3/n-6 PUFA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 37 publications
7
49
0
2
Order By: Relevance
“…Ahluwalia et al (1966) stated that degenerative changing occurs to the basofil cell from hipofisis grand toward rabbit that experiences fatty acid deficiency, it is caused by less of testosteron secretion. The result of this research is supported by (Yan, et al, 2013) that stated occur increasing level of GnRH, LH, FSH and rat testosteron that is given essential fatty acid supplemented with PUFA n-3 dan n-6 rasio in balance. Esmaeili et al…”
Section: March 2016supporting
confidence: 62%
“…Ahluwalia et al (1966) stated that degenerative changing occurs to the basofil cell from hipofisis grand toward rabbit that experiences fatty acid deficiency, it is caused by less of testosteron secretion. The result of this research is supported by (Yan, et al, 2013) that stated occur increasing level of GnRH, LH, FSH and rat testosteron that is given essential fatty acid supplemented with PUFA n-3 dan n-6 rasio in balance. Esmaeili et al…”
Section: March 2016supporting
confidence: 62%
“…Experiments carried out by other scientists demonstrated that the intake of n-3 fatty acids was beneficial to male reproductive capacity, resulting in histological and ultra-structural changes in the testis and sperm, better spermatogonial development, a larger number of germ cell layers (5), an increased total number of sperm per ejaculation, greater sperm quality, density and motility, as well as an increased membrane integrity of sperm in humans and animals (4,18,22,23,25,28), which may be related to changes in hormone metabolism (16 …”
Section: Resultsmentioning
confidence: 99%
“…The diameter of the testis in the control group was 29.85 cm, and that in the experimental group was 30 cm. When rams' diets contained n-3/n-6, the development of their testes was more intensive (16,28). The testicular parenchyma is a functional part of the testis and consists of two compartments: a tubular compartment and an interstitial one (21).…”
Section: Resultsmentioning
confidence: 99%
“…Again in boars, DHA and n-3 series fatty acids in sperm were positively correlated with motility (Am-in et al, 2011). Furthermore, in rats sperm motility was found to be positively correlated with the n-3/n-6 fatty acids ratio in the diet (Yan et al, 2013). Additionally, in humans sperm motility was negatively correlated to the seminal plasma concentration of n-6 series fatty acids (Safarinejad et al, 2010) and also in humans, motility has been positively correlated with the DHA levels in sperm (Nissen and Kreysel, 1983) although DHA supplementation does not affect human sperm motility (Conquer et al, 2000).…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, fatty acid supplementation in male European sea bass induced a longer spermiation period and higher milt spermatozoal concentrations ). Recently, a higher sperm concentration was found in rats fed a diet with a high n-3/n-6 fatty acid ratio (Yan et al, 2013). Moreover, in humans, sperm concentration has been positively correlated with DHA levels (Nissen and Kreysel, 1983).…”
Section: Discussionmentioning
confidence: 98%